Bacterial Vaginosis and the Natural History of Human Papillomavirus - King, Caroline C. (Hindawi Publishing Corporation, 2011)
Objective. To evaluate associations between common vaginal infections and human papillomavirus (HPV). Study Design. Data from up to 15 visits on 756 HIV-infected women and 380 high-risk HIV-uninfected women enrolled in the HIV Epidemiology Research Study (HERS) were evaluated for associations of bacterial vaginosis, trichomoniasis, and vaginal Candida colonization with prevalent HPV, incident HPV, and clearance of HPV in multivariate analysis. Results. Bacterial vaginosis (BV) was associated with increased odds for prevalent (aOR = 1.14, 95% CI: 1.04, 1.26) and incident (aOR = 1.24, 95% CI: 1.04, 1.47) HPV and with delayed clearance of infection (aHR = 0.84, 95% CI: 0.72, 0.97). Whereas BV at the preceding or current visit was associated with incident HPV, in an alternate model for the outcome of incident BV, HPV at the current, but not preceding, visit was associated with incident BV. Conclusion. These findings underscore the importance of prevention and successful treatment of bacterial vaginosis.